The invisibility of men in South African violence prevention policy: national prioritization, male vulnerability, and framing prevention - van Niekerk, Ashley; Tonsing, Susanne; Seedat, Mohamed; Jacobs, Roxanne; Ratele, Kopano; McClure, Roderick (Global health action, 2015)
South Africa has a significant violence problem. The exposure of girls and women to interpersonal violence is widespread, and the victimization of men, especially to severe and homicidal forms of aggression, is of considerable concern, with male homicide eight times the global rate. In the last two decades, there have been a plethora of South African policies to promote safety. However, indications suggest that the policy response to violence is not coherently formulated, comprehensive, or evenly implemented. This study examines selected South African national legislative instruments in terms of their framing and definition of violence and its typology, vulnerable populations, and prevention. This study comprises a directed content analysis of selected legislative documents from South African ministries mandated to prevent violence and its consequences or tasked with the prevention of key contributors to violence. Documents were selected using an electronic keyword search method and analyzed independently by two researchers. The legislative documents recognized the high levels of violence, confirmed the prioritization of selected vulnerable groups, especially women, children, disabled persons, and rural populations, and above all drew on criminological perspectives to emphasize tertiary prevention interventions. There is a policy focus on the protection and support of victims and the prosecution of perpetrators, but near absent recognition of men as victims. There is a need to broaden the policy framework from primarily criminological and prosecutorial perspectives to include public health contributions. It is likewise important to enlarge the conceptions of vulnerability to include men alongside other vulnerable groups. These measures are important for shaping and resourcing prevention decisions and strengthening primary prevention approaches to violence.